Desmoplakin Cardiomyopathy, a Fibrotic and Inflammatory Form of Cardiomyopathy Distinct From Typical Dilated or Arrhythmogenic Right Ventricular Cardiomyopathy. Issue 23 (9th June 2020) - Smith, Eric D.; Lakdawala, Neal K.; Papoutsidakis, Nikolaos; Aubert, Gregory; Mazzanti, Andrea; McCanta, Anthony C.; Agarwal, Prachi P.; Arscott, Patricia; Dellefave-Castillo, Lisa M.; Vorovich, Esther E.; Nutakki, Kavitha; Wilsbacher, Lisa D.; et al.
Abstract : Background: Mutations in desmoplakin ( DSP ), the primary force transducer between cardiac desmosomes and intermediate filaments, cause an arrhythmogenic form of cardiomyopathy that has been variably associated with arrhythmogenic right ventricular cardiomyopathy. Clinical correlates of DSP cardiomyopathy have been limited to small case series. Methods: Clinical and genetic data were collected on 107 patients with pathogenic DSP mutations and 81 patients with pathogenic plakophilin 2 ( PKP2 ) mutations as a comparison cohort. A composite outcome of severe ventricular arrhythmia was assessed. Results: DSP and PKP2 cohorts included similar proportions of probands (41% versus 42%) and patients with truncating mutations (98% versus 100%). Left ventricular (LV) predominant cardiomyopathy was exclusively present among patients with DSP (55% versus 0% for PKP2, P <0.001), whereas right ventricular cardiomyopathy was present in only 14% of patients with DSP versus 40% for PKP2 ( P <0.001). Arrhythmogenic right ventricular cardiomyopathy diagnostic criteria had poor sensitivity for DSP cardiomyopathy. LV late gadolinium enhancement was present in a primarily subepicardial distribution in 40% of patients with DSP (23/57 with magnetic resonance images). LV late gadolinium enhancement occurred with normal LV systolic function in 35% (8/23) of patients with DSP . Episodes of acute myocardial injury (chest pain with troponin elevation and normal coronary angiography) occurred in 15% of patients with DSP and were strongly associated with LV late gadolinium enhancement (90%), even in cases of acute myocardial injury with normal ventricular function (4/5, 80% with late gadolinium enhancement). In 4 DSP cases with 18F-fluorodeoxyglucose positron emission tomography scans, acute LV myocardial injury was associated with myocardial inflammation misdiagnosed initially as cardiac sarcoidosis or myocarditis. Left ventricle ejection fraction <55% was strongly associated with severe ventricular arrhythmias for DSP cases ( P <0.001, sensitivity 85%, specificity 53%). Right ventricular ejection fraction <45% was associated with severe arrhythmias for PKP2 cases ( P <0.001) but was poorly associated for DSP cases ( P =0.8). Frequent premature ventricular contractions were common among patients with severe arrhythmias for both DSP (80%) and PKP2 (91%) groups ( P =non-significant). Conclusions: DSP cardiomyopathy is a distinct form of arrhythmogenic cardiomyopathy characterized by episodic myocardial injury, left ventricular fibrosis that precedes systolic dysfunction, and a high incidence of ventricular arrhythmias. A genotype-specific approach for diagnosis and risk stratification should be used. Abstract : Supplemental Digital Content is available in the text.